The Mediating Role of Green Trust in the Effect of Green Perceived Value and Green Brand Image on Green Purchase Intention for Eco-Fashion in the Special Region of Yogyakarta - Ningsih, Lina Tusia; Sutiono, Heru Tri; Effendi, Mohamad Irhas (Strata International Journal of Social Issues, 2025)
This study investigates the mediating role of green trust in the relationship between green perceived value and green brand image on green purchase intention within the eco-fashion industry in the Special Region of Yogyakarta, Indonesia. Amid increasing environmental awareness and policy initiatives encouraging sustainable consumption, eco-fashion adoption remains low due to limited consumer trust and perceived environmental benefit. Using a quantitative, cross-sectional design, data were collected from 180 environmentally conscious individuals through a structured online questionnaire. The constructs—green perceived value, green brand image, green trust, and green purchase intention—were measured using validated instruments and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that both green perceived value and green brand image have a significant positive impact on green purchase intention and green trust. Furthermore, green trust mediates the effect of both independent variables on purchase intention, highlighting its central role in shaping consumer decisions in sustainable fashion contexts. These findings underscore the importance for eco-fashion brands to strengthen environmental value and credibility through transparent and ethical practices.